Coming home to Tibet : a memoir of love, loss, and belonging - Dhompa, Tshering Wangmo (b, 2016)
When her mother dies in a car accident along a great highway in India, far from her country and her family, Tsering decides to take a handful of her ashes to Tibet. She arrives at the foothills of her mother's ancestral home in a nomadic village in East Tibet to realize that she had been preparing for this homecoming all her life. Everything is familiar to her, especially the flowers of the Tibetan summer. She understands then the gift her mother had bequeathed her: the love of a land. A Home in Tibet is a daughter's haunting tribute to a mother and a homeland. A story about the love between a mother and a daughter who only had each other as family and refuge, it gestures to the journeys made by those exiled from their lands, and the dreams of daughters.
Keywords: Dhompa, Tsering Wangmo -- Travel -- China -- Tibet Autonomous Region; Mothers and daughters; Mothers -- Death